2012
DOI: 10.4102/hsag.v17i1.535
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of registered nurses regarding factors influencing service delivery in expanding programmes in a primary healthcare setting

Abstract: The aim of this study was to explore and describe the perceptions of registered nurses regarding factors influencing service delivery regarding expansion programmes in a primary healthcare setting, using a qualitative approach. The registered nurses, who have been working in the clinics for more than two years and have been exposed to the expansion programmes there, were purposively sampled. Two focus group interviews were conducted in a neutral place and the data collected by the researcher Nnoi A. Xaba (N.A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…The nursing managers both reacted and responded to the health system deficiencies in their own way, either by trying to cope with staff shortages or by responding creatively to the lack of water in rural clinics, through partnering with the local community. Other studies have also found that PHC clinic managers often balance operational management and service delivery to many patients amidst staff shortages in the health system ( 33 35 ). Although the diary entry on the lack of running water in some FS clinics appears to be an isolated incident, the lack of running water at rural clinics is a common finding in national infrastructure assessments ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nursing managers both reacted and responded to the health system deficiencies in their own way, either by trying to cope with staff shortages or by responding creatively to the lack of water in rural clinics, through partnering with the local community. Other studies have also found that PHC clinic managers often balance operational management and service delivery to many patients amidst staff shortages in the health system ( 33 35 ). Although the diary entry on the lack of running water in some FS clinics appears to be an isolated incident, the lack of running water at rural clinics is a common finding in national infrastructure assessments ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, there have been a number of studies that focus on nurses working at PHC facilities ( 32 – 37 ). However, the majority of these tend to focus on registered nurses (with 4 years of training) who are the direct service providers ( 33 35 , 37 ), rather than on PHC clinic managers.…”
mentioning
confidence: 99%
“…These range from the limitation of provision and access to services, to service providers changing jobs to facilities where they perceive to be more secure [14,15,25,26,45]. Low retention of public sector nurses in South Africa has been related to lack of security in the public facilities [25].…”
Section: Discussionmentioning
confidence: 99%
“…Risk management practices are used when one nds oneself in a dangerous situation and/or location and takes precautionary measures to be a less suitable target for victimization [22,24]. These concepts, though mostly originating from higher-income countries, support transferable principles to low and middle-income contexts, where women are even perceived as more vulnerable and of comparably lower socioeconomic status, especially in the rural areas [14,15,25,26]. This paper explores the role of health facility security and feeling of safety, which determine the provision and uptake of health services respectively, from the perspective of health staff, who were all females and health service users (pregnant women).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of security in facilities (absence of perimeter fencing, inadequate lighting, lack of within-facility accommodation and absence of security guards) have raised issues of access across some other LMICs (Tanzania, Nepal, Swaziland, South Africa and Kenya) to varying degrees, especially in the rural areas. These range from the limitation of provision and access to services, to service providers changing jobs to facilities where they perceive to be more secure [14,15,25,26,45]. Low retention of public sector nurses in South Africa has been related to lack of security in the public facilities [25].…”
Section: Discussionmentioning
confidence: 99%